Challenges in Academic Essay Structuring: An Error Analysis of EFL Learners - Musiman Musiman; Meida Fitriana (EXPOSE (Journal of English Education and for Specific Purpose), 2024)
Academic essay writing remains a challenging skill for learners of English as a Foreign Language (EFL), particularly in higher education contexts. This study aims to analyze the types of structural errors found in students English essays at Universitas Muhammadiyah Lampung. Employing a descriptive qualitative research design with an error analysis approach, the data were collected from 14 essays written by undergraduate students enrolled in an English writing course. The essays were analyzed based on structural components of academic essay writing, including the introduction, body paragraphs, and conclusion.The findings reveal that structural errors occur across all components of the essays, with the highest frequency found in the body paragraphs. Common problems include the absence of clear topic sentences, insufficient supporting details, and weak coherence between ideas. In the introduction section, several students failed to present a clear thesis statement, while conclusions often lacked effective summarization and closing statements. These structural weaknesses indicate that students experience greater difficulty in organizing ideas than in using grammatically accurate language.Overall, the study suggests that students essay writing problems are primarily related to discourse-level organization rather than linguistic accuracy. The findings highlight the importance of explicit instruction focusing on essay structure and paragraph development to improve students academic writing competence. This study contributes to EFL writing research by providing context-specific insights into structural errors in academic essays and offers pedagogical implications for improving writing instruction in higher education.